ANALISIS POSTUR TUBUH PEKERJA MANUAL MATERIAL HANDLING DENGAN PENDEKATAN OWAS (OVACO WORKING POSTURE ANALYSIS SYSTEM) DI INDAH PROPERTY - Sri Zetli (JURNAL REKAYASA SISTEM INDUSTRI, 2017)
In the small and medium enterprises, the human factor is still very important in determining the productivity of a production system. However, safety and comfort are often overlooked, as is the case with profile companies in Indah Property. This is influenced by the condition of the company's work facilities that are less ergonomic, so it can endanger the worker's body. This study aims to identify and analyze the worker's posture in the printing and shipping department using the Ovako Working Posture Analysis System (OWAS) method. This study begins by evaluating workers' posture with and analyzing by OWAS method. From the OWAS method, worker attitudes of the Department of Printing are less than 50% of all workers classified as category 2. The work attitude in the Delivery Department is categorized as 4 by 57.14% for Dedi workers. While corrective action on the Department of Printing on the segment bending, bending and twisting, bending forward and sideways, the legs are standing resting on both legs straight, standing on one straight leg, with category 2 fixing in the future and category 3 that fix as soon as possible . At the Delivery Department for bending, twisting and tilting, bending and twisting, bending forward and sideways, standing resting on both legs with bent knees, standing resting on both legs with bent knees, kneeling on one leg or both knees, with category 2 ie fixing in the future and category 3 that is fixing as soon as possible.